The Concept of Islamic Worldview According to Hamid Fahmy Zarkasyi - Irwan Haryono S; Abdul Aziz Sebayang (Civiliza Publishing, Indonesia., 2026)
The concept of Islamic Worldview is an important discourse in the study of contemporary Islamic philosophy because it functions as an epistemological and ontological framework in understanding the reality of life. In the midst of globalization and the dominance of the secularism paradigm that tends to separate religion from social, economic, and political life, understanding the Islamic worldview is becoming increasingly relevant. The Islamic Worldview offers an integrative perspective that places revelation as the primary source of knowledge and makes monotheism a fundamental principle in all aspects of human life. This research aims to analyze the concept of Islamic Worldview according to Hamid Fahmy Zarkasyi and explain its relevance in facing the challenges of the contemporary world, especially in the aspects of ontology, epistemology, and axiology. This study uses a qualitative method with a library research approach. Data were obtained from the works of Hamid Fahmy Zarkasyi and Syed Muhammad Naquib al-Attas as well as relevant academic journal literature. The analysis was carried out through a content analysis method with a historical and sociological approach to understand the development of the concept of Islamic Worldview in the Islamic intellectual tradition. The results of the study show that the Islamic Worldview, according to Zarkasyi, is a holistic paradigm of life based on monotheism. This paradigm rejects the dichotomy between religion and world life and emphasizes the integration of revelation, reason, and social reality in the Islamic knowledge system. This concept is relevant as the basis for the development of a paradigm of science, education, and social life based on the values of monotheism in facing the challenges of modernity and globalization.